2021
DOI: 10.1007/s00420-021-01793-w
|View full text |Cite
|
Sign up to set email alerts
|

Back pain occurred due to changes in routinary activities among Brazilian schoolteachers during the COVID-19 pandemic

Abstract: Objective This study’s main objective was to investigate the emergence of back pain as a consequence to changes in usual activities due to the COVID-19 pandemic among teachers in public schools in the state of Minas Gerais, Brazil. Methods A cross-sectional study was conducted among 15,276 schoolteachers using an online questionnaire. The variables included sociodemographic and occupational data, health situation, habits and behaviors during the COVID-19 pandemic. Bivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
7
0
3
Order By: Relevance
“…Similarly, a study of public school teachers from Brazil found the appearance of back pain in 57.8% of the participants as a consequence of the change in routine activities due to the COVID-19 pandemic (20) . The regression analysis presented by the authors shows the association between back pain and female gender as well as with the teaching seniority (16 years or more), which is similar to what was observed in this work.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, a study of public school teachers from Brazil found the appearance of back pain in 57.8% of the participants as a consequence of the change in routine activities due to the COVID-19 pandemic (20) . The regression analysis presented by the authors shows the association between back pain and female gender as well as with the teaching seniority (16 years or more), which is similar to what was observed in this work.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, more than 84% of those surveyed presented some problem related to sleep quality, requiring attention and/or medical treatment, being well above that reported by López-García et al, Crepaldi et al and Freitas et al [ 5 , 6 , 47 ]. Preliminary reports suggest that professors present sleep problems, such as daytime sleepiness [ 55 ] and insomnia [ 56 ], an issue that has been aggravated by the transition to RW, reduction in financial stability [ 13 , 57 ] and PA practice [ 57 ] due to confinement, which obliges the professors to take several jobs, extending their working hours and workload, with the consequent affectation of their quality of life [ 55 , 56 ] and perceived stress [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic containment strategies, including lockdowns, social withdrawal, and remote working, have a significant impact on daily (working) life [2] . The aforementioned penalties, particularly remote working, contributed to lengthy periods of sitting, which facilitated not only musculoskeletal problems [14] , [19] but also the development of metabolic disorders like diabetes and cardiovascular diseases [5] , [10] .…”
Section: Discussionmentioning
confidence: 99%